High dose PPI-amoxicillin dual therapy for the treatment of Helicobacter pylori infection: a systematic review with meta-analysis. (July 2020) - Zhu, Yang-Jie; Zhang, Yi; Wang, Ting-Yi; Zhao, Jing-Tao; Zhao, Zhe; Zhu, Jian-Ru; Lan, Chun-Hui
Background: Helicobacter pylori resistance to amoxicillin remains rare in many regions. Proton pump inhibitor-amoxicillin-containing high dose dual therapy (HDDT) has been proposed to treat H. pylori infection. We aimed to assess the effectiveness and safety of PPI-amoxicillin HDDT for treatment of H. pylori infection in comparison with other regimens. Methods: Databases, including PubMed, Embase, and the Cochrane Register of Controlled Trials, were searched to find relevant publications. Randomized controlled trials comparing HDDT with control regimens for H. pylori eradication in adult patients were included. The primary outcome was eradication rate by intention-to-treat analysis. Adverse events were analyzed as second outcome. Results: A total of 15 trials with 3818 patients qualified for inclusion. The eradication rate of HDDT was neither significantly inferior nor superior to the recommended regimens such as triple therapy, bismuth quadruple therapy, and non-bismuth quadruple therapy [relative risk (RR): 1.00, 95% confidence interval (CI): 0.96–1.05, p  = 0.870]. This finding was robust through subgroup analyses and sensitivity analyses. Trial sequential analysis showed that HDDT was equivalent to control regimens, and further similar trials were unlikely to alter the conclusions of this analysis. The frequency of adverse events was significantly lower in HDDT group (RR: 0.48, 95% CI: 0.37–0.64, p  < 0.001). Conclusion: HDDT was equivalent to recommended first-line or rescue regimens with fewer adverse effects. The evidence from this meta-analysis supports the use of HDDT as first-line or rescue treatment for H. pylori infection. Trial registration: PROSPERO CRD42019133002